Construction Of Identity And Group Dynamics In The Cyberspace (Case Study On Komunitas Blogger Jogja And Komunitas Blogger Semarang ‘Loenpia Dot Net’) - Ayu Amalia, Ayu Amalia; Sukmono, Filosa Gita (2015)
Media convergence, “packed” the world to become more ‘compact’ and ‘operable’, enabling people to do their works simultaneously. Media convergence also encouraged people to go through a 'cultural shift', regarding the virtual world as an alternate world. It is not surprising that people possess multiple identities; the one which is exhibited in a public space, and another identity which is dedicated to cyberspace. This constructed identity distinguishes a group of digital natives and digital immigrants in ’cyberspace’.